Comparative analysis of cholesterol and hemoglobin levels in dewormed and non-dewormed school-age children - Nuril Sofiantin; Marisca Jenice Sanaky; Hardyansa; Army Dwi Israyanti (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction: Helminth infections continue to be a significant public health concern among school-age children, particularly in areas with inadequate sanitation. Chronic helminthiasis can impair nutrient absorption, disrupt lipid metabolism, and contribute to anemia. Regular deworming is recommended as a preventive strategy, yet evidence regarding its biochemical impact on cholesterol and hemoglobin levels remains limited. This study aimed to compare cholesterol and hemoglobin levels between dewormed and non-dewormed school-age children. Methods: A comparative descriptive design was employed involving 30 school-age children, consisting of 15 who routinely consumed deworming medication and 15 who did not. Blood samples were collected by trained health personnel and analyzed in a clinical laboratory. Hemoglobin levels were measured using a photometric method, while total cholesterol levels were determined using an enzymatic method. Descriptive analysis was used to compare mean values between groups. Results: Children who routinely consumed deworming medication showed lower mean cholesterol levels (152.9 mg/dL) compared with the control group (169.7 mg/dL). Mean hemoglobin levels were also higher in the dewormed group (12.31 g/dL) than in the non-dewormed group (11.86 g/dL). Although not all children fell within the normal reference ranges, the dewormed group demonstrated more stable biochemical profiles overall. These findings suggest that regular deworming may support healthier lipid metabolism and maintain hemoglobin levels within acceptable limits. Conclusion: The results suggest that periodic deworming has a positive impact on the biochemical status of school-age children. A reduced helminth burden may improve nutrient absorption, stabilize lipid profiles, and prevent chronic blood loss, which can lead to anemia. However, variations between individuals highlight the role of external factors such as diet, sanitation, and reinfection risk. Regular deworming appears to promote better cholesterol and hemoglobin profiles among school-age children, underscoring its importance in child health programs.